Effects of Root–Root Interactions on the Physiological Characteristics of Haloxylon ammodendron Seedlings - Huifang Yang; Suwan Ji; Deyan Wu; Menghao Zhu; Guanghui Lv (Plants, 2024)
The root traits and response strategies of plants play crucial roles in mediating interactions between plant root systems. Current research on the role of root exudates as underground chemical signals mediating these interactions has focused mainly on crops, with less attention given to desert plants in arid regions. In this study, we focused on the typical desert plant Haloxylon ammodendron and conducted a pot experiment using three root isolation methods (plastic film separation, nylon mesh separation, and no separation). We found that (1) as the degree of isolation increased, plant biomass significantly increased (p < 0.05), while root organic carbon content exhibited the opposite trend; (2) soil electrical conductivity (EC), soil total nitrogen (STN), soil total phosphorus (STP), and soil organic carbon (SOC) were significantly greater in the plastic film and nylon mesh separation treatments than in the no separation treatment (p < 0.05), and the abundance of Proteobacteria and Actinobacteriota was significantly greater in the plastic film separation treatment than in the no separation treatment (p < 0.05); (3) both plastic film and nylon mesh separations increased the secretion of alkaloids derived from tryptophan and phenylalanine in the plant root system compared with that in the no separation treatment; and (4) Pseudomonas, Proteobacteria, sesquiterpenes, triterpenes, and coumarins showed positive correlations, while both pseudomonas and proteobacteria were significantly positively correlated with soil EC, STN, STP, and SOC (p < 0.05). Aurachin D was negatively correlated with Gemmatimonadota and Proteobacteria, and both were significantly correlated with soil pH, EC, STN, STP, and SOC. The present study revealed strong negative interactions between the root systems of H. ammodendron seedlings, in which sesquiterpenoids, triterpenoids, coumarins, and alkaloids released by the roots played an important role in the subterranean competitive relationship. This study provides a deeper understanding of intraspecific interactions in the desert plant H. ammodendron and offers some guidance for future cultivation of this species in the northwestern region of China.